1972
DOI: 10.1084/jem.135.6.1293
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Idiotypic Specificities in Adult Mice by Administration of Antiidiotypic Antibody

Abstract: It has previously been shown that there are extensive idiotypic cross-reactions among antiphenylarsonate antibodies of A/J mice. The present work indicates that administration, into normal, adult A/J mice, of rabbit antiidiotypic antibody directed to A/J antiphenylarsonate antibody suppresses almost completely the subsequent production of antibody of the corresponding idiotype. No effect was noted on the formation of antibodies to the protein carrier or of antiphenylarsonate antibody of a different idiotype. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
91
1

Year Published

1973
1973
1993
1993

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 251 publications
(101 citation statements)
references
References 15 publications
9
91
1
Order By: Relevance
“…This is a positive interaction similar to a proliferative response to antigen. Administration of anti-idiotypic antibodies can both enhance (Eichmann and Rajewsky, 1975;Vakil and Kearny, 1986;Bernabe et al, 1981) and suppress (Hardt et al, 1972;Eichmann, 1974;Vakil and Kearny, 1986) the idiotypic immune response. Because all populations are identical in our model, and because idiotypic are symmetric, we have no a priori basis to discriminate between stimulatory and inhibitory interactions.…”
Section: A New Networkmentioning
confidence: 99%
“…This is a positive interaction similar to a proliferative response to antigen. Administration of anti-idiotypic antibodies can both enhance (Eichmann and Rajewsky, 1975;Vakil and Kearny, 1986;Bernabe et al, 1981) and suppress (Hardt et al, 1972;Eichmann, 1974;Vakil and Kearny, 1986) the idiotypic immune response. Because all populations are identical in our model, and because idiotypic are symmetric, we have no a priori basis to discriminate between stimulatory and inhibitory interactions.…”
Section: A New Networkmentioning
confidence: 99%
“…Jerne (15) suggested that an Id network maintains the homeostasis of the immune response. It was proposed that Id and anti-Id can manipulate cellular and humoral immunity (6,22). An anti-Id antibody bearing the internal image of external antigen has been demonstrated and used for the induction of specific immune response (10,18,19).…”
mentioning
confidence: 99%
“…An anti-Id antibody bearing the internal image of external antigen has been demonstrated and used for the induction of specific immune response (10,18,19). In various antigenic systems, the injection of Ab2 modified the production of Ab 1 expressing the corresponding Id (6,8,23). In some systems, preinjection with Ab2 specifically suppressed the production of the given Ab 1 (6,8).…”
mentioning
confidence: 99%
See 2 more Smart Citations